BioImpedance Spectroscopy to maintain Renal Output: the BISTRO randomised controlled trial - Simon J Davies; David Coyle; Elizabeth Lindley; David Keane; John Belcher; Fergus Caskey; Indranil Dasgupta; Andrew Davenport; Ken Farrington; Sandip Mitra; Paula Ormandy; Martin Wilkie; et al. (Health Technology Assessment, 2025)
Background Fluid removal is a key component of dialysis treatment but, if excessive, can result in a faster decline in residual kidney function. Prescribing the optimal removal of fluid on dialysis to avoid this is therefore important. Bioimpedance spectroscopy, a bedside device that estimates tissue hydration, might improve this prescription, so reducing the rate of decline in kidney function and improving patient outcomes. We wished to establish the efficacy and cost-effectiveness of bioimpedance in pursuing this treatment strategy. Methods We undertook a multicentre, open-label, parallel, individually randomised controlled trial in incident haemodialysis patients, with clinicians and patients blinded to bioimpedance readings in the control group. Eligible patients had a urine output of > 500 ml/day or a glomerular filtration rate > 3 ml/minute/1.73 m2. Randomisation was 1 : 1 using a concealed automated computer-generated allocation system stratified by centre. Clinical assessments were made monthly for 3 months and then every 3 months for up to 24 months using a standardised proforma in both groups, supplemented in the intervention group by the bioimpedance estimate of the normally hydrated weight. The primary outcome was time to anuria; secondary outcomes were rate in decline of residual kidney function, blood pressure, dialysis-related symptoms (Integrated Palliative Care Outcome Scale-Renal), quality of life (EuroQol) and incremental cost per additional quality-adjusted life-year gained. Results Four hundred and thirty-nine patients were recruited and analysed from 34 United Kingdom centres. There were no between-group differences in cause-specific hazard rates of anuria, 0.751 (95% confidence interval 0.459 to 1.229) or subdistribution hazard rates 0.742 (95% confidence interval 0.453 to 1.215). Kidney function decline was slower than anticipated, pooled linear rates in year 1: −0.178 (95% confidence interval −0.196 to −0.159) ml/minute/1.73 m2/month; year 2: −0.061 (95% confidence interval −0.086 to −0.036) ml/minute/1.73 m2/month. Longitudinal blood pressure, symptoms and patient-reported outcomes did not differ by group. The intervention was associated with £382 (95% confidence interval −£3319 to £2556) lower average cost per patient (price year 2020) and 0.043 (95% confidence interval −0.019 to −0.105) more quality-adjusted life-years and no harm compared to control. A post hoc 5-year analysis found better survival with more residual kidney function at enrolment and at any time over the next 2 years. Conclusion The use of a standardised clinical protocol for fluid assessment to avoid excessive fluid removal is associated with excellent preservation of residual kidney function and better medium-term survival in this cohort. Bioimpedance measurements are not necessary to achieve this. Probability of the intervention being cost-effective was 76% and 83% at the willingness-to-pay thresholds of £20,000 and £30,000 per quality-adjusted life-year gained, respectively. Limitations The trial did not recruit to target (85%), and the number of primary outcomes was fewer than predicted. The trial was interrupted by coronavirus disease discovered in 2019, during which 193 (6.7%) fluid assessments and 276 (8.1%) kidney function measures but no primary outcomes were missed. Future work Associations between age, ethnicity and the decline in residual kidney function require further investigation. BioImpedance Spectroscopy to maintain Renal Output identified centre-level variation in practices related to fluid management in haemodialysis that require evaluation. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number 14/216/01. Plain language summary Why did we do this trial? Usually, people starting haemodialysis treatment still have some of their own kidney function. Keeping this going for as long as possible brings benefits, including fewer symptoms and better quality of life. We wanted to know if using a device called bioimpedance, which measures the amount of fluid in the body, can help decide how much fluid should be removed during a dialysis session, as avoiding removing too much might slow down the loss of remaining kidney function. What did we do? We undertook a trial in which we compared two approaches to deciding how much fluid should be removed during a dialysis treatment. In both groups, clinicians used a checklist of things they should consider when making this decision, and in one group, they also had an estimate of the body fluid content from the bioimpedance device. We enrolled 439 patients from half of United Kingdom dialysis centres and measured their decline in kidney function, blood pressure, symptoms, quality of life and use of health services over the next 2 years. What did we find? There was no difference between the groups in the decline of kidney function, blood pressure or symptoms. In both groups, the speed of kidney function loss was half what we anticipated, with one quarter losing it by 2 years, rather than 1 year as expected. There was significant uncertainty in estimating any cost saving and the quality-adjusted life-years experienced by patients. Better preservation of kidney function was associated with better survival. What does this mean? Remaining kidney function when starting dialysis is better maintained than previously thought, possibly because much greater attention was paid to it. Using bioimpedance did not benefit the loss of kidney function, but it was not harmful and may have other small advantages. This trial is registered as ISRCTN11342007.